Osservare la didattica in aula. Un'esperienza nella scuola secondaria di I grado - Giorgio Asquini (LED Edizioni Universitarie, 2018)
The paper presents a study of Training-Research coordinated by Sapienza, Università di Roma, in collaboration with a lower secondary school in Rome. Two cycles of systematic classroom observations were carried out, each one for a full weekly lesson timetable, in 4 eighth grade classes. Student-Observers (enrolled in the bachelor degree in Educational Sciences), were specifically trained for the research and have always worked in pairs to ensure the quality of data collected. The observations were categorized, distinguishing the different didactic and organizational aspects and counting the amount of time dedicated to each type of school activity. Some of the key findings regarding the observations are presented and discussed: the comparison between the classes on the school functions, the incidence of constructivist teaching compared to traditional lesson, the balance between the written tests and oral questions. Other data insights and the impact of research on the professional training of teachers are considered.